Prevalence of Antibiotic Use in Hospitalized COVID-19 Patients: An Observational Study in Secondary Healthcare Hospitals in Kosovo - Tolaj, Ilir; Fejza, Hajrullah; Alidema, Fitim; Mustafa, Lirim (IIUM Medical Journal Malaysia, 2024)
INTRODUCTION: Globally, the high use of antibiotics among hospitalized patients diagnosed with COVID-19 has been reported despite evidence that bacterial coinfections are uncommon. This issue raised our concerns, as there was a report on high frequency of antibiotic resistant bacterial infections in COVID-19 patients admitted to the intensive care unit. Thus, we conducted a study to determine the prevalence of antibiotic use for hospitalized acute COVID-19 infection in secondary healthcare hospitals in Kosovo. MATERIALS AND METHODS: A cross sectional study was conducted among patients with acute COVID-19 admitted to secondary healthcare hospitals in Kosovo. A modified Infectious Diseases International Research Initiative (ID-IRI) questionnaire was used to collect information in 460 COVID-19 PCR positive patients. RESULTS: All studied patients (100%) were treated with antibiotics. An empirical antibiotics were used to cover Methicillin-resistant Staphylococcus aureus (MRSA) infections in 136 cases (29.6%), methicillin-susceptible Staphylococcus aureus (MSSA) infections in 86 cases (18.7%), atypical pathogen in 174 cases (37.8%), and Pseudomonas infections in 48 cases (10.4%). The most frequently used antibiotics were ceftriaxone/cefotaxime plus macrolide (149 cases; 31%), ceftriaxone/cefotaxime plus quinolone (85 cases; 17.7%), and co-amoxiclav plus fluoroquinolone (78 cases; 16.3%). Imipenem was most frequently used in the ICU (64 cases; 13.3%). CONCLUSION: Despite the antibiotic guidelines clearly stated that antibiotics should only be used in confirmed case of secondary bacterial infections including the COVID-19 patients, our study revealed that the overused of antibiotics remained unchanged. As the misused and overused of antibacterial has been shown to accelerate the emergence and spread of antibacterial resistant, the inappropriate practice should be changed.